Omalizumab therapy in a patient with cronic spontaneous urticaria, ulcerative colitis, hypereosinophilia and prurigo Besnier: a case report. (14th December 2018) - Grieco, T.; Chello, C.; Faina, V.; Gomes, V. V.; Alei, L.; Sernicola, A.; Panasiti, V.; Calvieri, S.
Abstract: The case of a woman who suffered from CSU and prurigo Besnier, with a history of chronic hyper-eosinophilia, ulcerative colitis and thyroiditis, unresponsive to anti-histamines and steroids is reported. The patient received omalizumab treatment, and obtained resolution of urticaria along with improvement of cutaneous symptoms of prurigo.